Analysis of Alkalinity Water Quality in Situbondo Intensive Pond Waters (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2023)
Situbondo regency is one of the regencies located on the north coast of east java province which has potential in the fisheries and marine sectors. The sea area in Situbondo Regency is 1,142.4 km2. Geographically, these potential areas are concentrated in coastal areas with fishing, pond aquaculture, freswater aquaculture, seawater aquaculture, hatcheries and fishery prosessing businesses. Aquaculture businesses growing rapidly in Situbondo Regency, namely vaname shrimp aquaculture. The survival of vaname shrimp is influenced by the quality of water used. Alkalinity is one of the water quality parameters that impartant in the growth of vaname shrimp. Alaklinity that is to low will cause the shrimp can change their shells or molt  frequently. Shrimp tat molt too often will be susceptible to disease and the threat of cannibalism due to the weak condition of the shrimp. In addition , too low alkalinity can also cause the shrimp fail to molt so that the shrimp can die. Besides that, if the alkalinity is too high, it will be difficult for the shrimp to molt so that their growth is not optimal. Water quality testing with alakalinity parameter was caried out at several pond location as samples, namely location 1 in Demung village, besuki district, location 2 in Kilensari village, Panarukan district, location 3 in Sletreng village , Kapongan district dan location 4 in Agel Village, Jangkar district. The research was conducted for 1 year with testing every 2 weeks. The result of measurements of alkalinity in Situbondo waters from november until November 2022 were ini the range of 90- 145 ppm. Thies value is still classified as appropriate to support pond-based shrimp farming based on water quality standart by PERMENT KP No.75 of 2016 concerning general duidelines for shrimp aquaculture stating that the level of alkalinity in water should be range of 80- 150 ppm. Meanwhile, number of Ca2+ level that support hardness are also in safe range for the survival of vaname shrimp, which below 500 ppm.  Keyword : Alkalinity, Water Quality, Pond